(untitled) (Global Journal of Human-Social Science, 2015)
Entrepreneurship education is a teaching philosophy and model needs to adapt to economic, social and national development strategies. In-depth analysis of the reasons for the lack of entrepreneurship education is made in this paper, as well as how to implement entrepreneurship education. The writer proposes concrete measures to promote the healthy development of China’s college entrepreneurship education.